Java web services up and running - Kalin, Martin (Beijing Sebastopol, Calif. O'Reilly, 2009)
Introduction to Java's APIs for both XML Web Services (JAX-WS and RESTful Web Services (JAX-RS) provides a pragmatic approach, architectural overview, working code examples, and instructions for compiling, deploying, and executing an application. -- from cover, p.4.
Java web services quickstart -- All about WSDLs [Web Service Definition Language] -- SOAP handling [Simple Object Access Protocol] -- RESTful web services [JAX-RS] -- Web services security -- JAX-WS in Java application servers -- Beyond the flame wars.
Includes index.
"Covers JAX-WS 2.1" -- Cover, p.1.
Keywords: Web site development; Java (Computer program language); Application software -- Development